Risk factors profile for liver damage in cardiac inpatients - Jovanović, Jovan; Milovanović, Dragan R.; Sazdanović, Predrag; Sazdanović, Maja; Radovanović, Milan; Novković, Ljiljana; Zdravković, Vladimir; Zdravković, Nemanja; Simić, Ivan; Ružić Zečević, Dejana; Janković, Slobodan M. (Vojnosanitetski pregled, 2021)
Background/Aim. Liver damage, with potentially serious consequences, is not uncommon in hospitalized cardiac patients. The aim of our study was to determine the risk factor profile for liver damage in patients hospitalized from a deterioration of their acute or chronic cardiac illness. Methods. The study had observational case-control design with retrospective data collections from medical files of adult patients hospitalized in a tertiary health care center. The cases (n = 140) were subjects with novel liver injury (which emerged during hospital stay) and three control subjects were matched (age, date) for each case subject (n = 420). The primary outcome was hepatotoxicity (present or absent) and independent variables were proposed risk factors. Statistical analysis included descriptive methods, hypothesis testing and univariate and multivariate binary logistic regression, with p ≤ 0.05. Results. In the whole study population, there were 432 (77.1%) females and the mean age of patients was 64.1 years [standard deviation (SD) = 10.7, range 24–85 years]. The most common illnesses were coronary heart disease (n = 385), hypertension (n = 334) and arrhythmia (n = 115). Mean value of Charlson Comorbidity Index (CCI) score was 3.8 (SD=1.7; range 1-10) corresponding to estimated CCI 10-years survival rate of 54.4% (SD = 33.5%). In the group of cases, 114 (81.4%) of the patients had hepatocellular, 9 (6.4%) cholestatic and 17 (12.2%) mixed type of hepatic injury. Factors independently associated with hepatotoxic event were previous occasional alcohol intake odds ratio (OR) 96.47; 95% confidence interval (CI) 28.95–321.43; p
Keywords: alcohol drinking; amiodarone; cardiovascular diseases; chemical and drug induced liver injury; drug toxicity; inpatients; obesity; risk factors